Do-Not-ResuscitateDecision-Making during the COVID-19 Pandemic in a Teaching Hospital: Lessons Learned for the Future - Mick van de Wiel; Sabrina van Ierssel; Walter Verbrugghe; Veerle Mertens; Annelies Janssens (Journal of Aging Research)
Rationale. Contribute to the understanding of DNR decision-making and conducting end-of-life conversations, about which there is a paucity of data available in the current literature. Aims and Objectives. Assess how the decision-making process to determine a DNR code is implemented in the day-to-day clinical practice in a tertiary teaching hospital. Familiarity with the use of different scores as a possible objective support for DNR decisions and the influence of various elements on a DNR decision was explored. Method. A cross-sectional survey study was conducted between February 2021 and April 2021 for all doctors and doctors in training, working in the Antwerp University Hospital during the COVID-19 pandemic. Results. 127 doctors participated in this study. The familiarity with the different scores used in the triage during the COVID-10 pandemic was 51% for the Clinical Frailty Scale (CFS) and 20% for the Charlson Comorbidity Index (CCI). Participants indicated that their DNR decision is based on various aspects such as clinical assessment, comorbidities, patient’s wishes, age, prognosis, and functional state. Conclusion. The familiarity with the different scores used during triage assessments is low. The total clinical picture of the patient is needed to make a considered decision, and this total picture of the patient seems to be well encompassed by frailty measurement (CFS). Although many participants indicated that the different scores do not offer much added value compared to their clinical assessment, it can help guide DNR decisions, especially for doctors in training.